2022
DOI: 10.3233/jad-215394
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Accuracy of Cognitive Screening Tests in Detecting Dementia Associated with Alzheimer’s Disease: A Hierarchical Bayesian Latent Class Meta-Analysis

Abstract: Background: Montreal Cognitive Assessment (MoCA) and Mini-Mental State Examination (MMSE) are neuropsychological tests commonly used by physicians for screening cognitive dysfunction of Alzheimer’s disease (AD). Due to different imperfect reference standards, the performance of MoCA and MMSE do not reach consensus. It is necessary to evaluate the consistence and differentiation of MoCA and MMSE in the absence of a gold standard for AD. Objective: We aimed to assess the accuracy of MoCA and MMSE in screening AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 95 publications
1
2
0
Order By: Relevance
“…In addition, the results of this study in the ADNI population are consistent with the findings of previous meta-analyses that investigated the diagnostic performance of the MOCA and MMSE for detecting AD and MCI due to AD under non-gold standard conditions using a hierarchical Bayesian latent class meta-analysis [ 23 , 24 ]. In that study, the MoCA demonstrated a sensitivity of 0.934 and a specificity of 0.899 in detecting AD, while the MMSE had a sensitivity of 0.883 and a specificity of 0.903 [ 23 ]. For the detection of MCI, the MoCA showed a sensitivity of 0.85 and a specificity of 0.79, whereas the MMSE had a sensitivity of 0.71 and a specificity of 0.71 [ 24 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, the results of this study in the ADNI population are consistent with the findings of previous meta-analyses that investigated the diagnostic performance of the MOCA and MMSE for detecting AD and MCI due to AD under non-gold standard conditions using a hierarchical Bayesian latent class meta-analysis [ 23 , 24 ]. In that study, the MoCA demonstrated a sensitivity of 0.934 and a specificity of 0.899 in detecting AD, while the MMSE had a sensitivity of 0.883 and a specificity of 0.903 [ 23 ]. For the detection of MCI, the MoCA showed a sensitivity of 0.85 and a specificity of 0.79, whereas the MMSE had a sensitivity of 0.71 and a specificity of 0.71 [ 24 ].…”
Section: Discussionsupporting
confidence: 88%
“…We obtained the priors for sensitivity and specificity of each test by previous literatures [ 23 25 ], and the priors for prevalence of AD and MCI due to AD were from review reports [ 1 , 5 ]. The specific details of informative prior distributions for the parameters in the models are presented in Table 3 .…”
Section: Methodsmentioning
confidence: 99%
“…These cognitive measures can also be time-consuming, not education-fair, not culturally-fair, and may need well-trained interviewers to ensure standardized and reliable outcomes ( Baldo et al, 2013 ; Li et al, 2012 ; Nasreddine et al, 2004 ; Turana & Handajani, 2011 ). Measures such as the MMSE and MoCA demonstrate good screening properties for Alzheimer’s disease (AD), however, language, educational attainment, literacy, and country of study introduces significant sources of heterogeneity and error ( Wang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%